A general strategy for C(sp3)–H functionalization with nucleophiles using methyl radical as a hydrogen atom abstractor - Isabelle Nathalie-Marie Leibler (Nature Portfolio, 2021)
When carbon-based units are functionalized in photoredox catalysis, electrophilic coupling partners are often used, such that the polarities of the two fragments are appropriately matched. Here the authors show a generalized methodology to instead use nucleophilic coupling partners, which are cheaper and often simpler, via successive hydrogen atom transfer and oxidative radical-polar crossover.